Spin Properties and Metal-Semiconductor Transition of Nitrogen-Containing Zigzag Graphyne Nanoribbon Caused by Magnetic Atom Doping - Min, Zi-Cong; Peng, Xiao-Fang; Tan, Shi-Hua (Frontiers in Materials, 2022)
In this study, the density function theory (DFT) was used to study the influence of the magnetic atoms (Fe, Co, Ni) doping on the electrical properties of nitrogen-containing zigzag graphyne-like nanoribbon (N-ZGyNR). The results show that, by doping different atoms into the natural “holes” of N-ZGyNR, the changes in the structure, magnetic moment distribution and electrical properties of N-ZGyNR are different. Due to the incomplete saturation of the edge C atoms, the initial N-ZGyNR presents metallicity and spin degeneracy. The doping of Fe atoms will cause the C-C bond in N-ZGyNR to be completely broken, resulting in structural distortion, and about 0.8e- will transfer from Fe to N-ZGyNR. Compared with Fe doping, Co/Ni doping has a smaller effect on the N-ZGyNR and will not cause structural distortion, but will redistribute the spin charge in N-ZGyNR, thereby forming a band gap of 60 meV near the Fermi level to realize the transition of metal-semiconductor. The above results show that the electrical properties of N-ZGyNR can be controlled by magnetic atom doping, and the metal-semiconductor transition can be realized by Co/Ni doping, which provides a new alternative for spintronic devices.